Developing a distance-based doctoral supervisory model: Inquiry over disrupted trajectories - Qi GY; Skyrme G; White CJ (Taylor and Francis Group, 2023)
This paper proposes a distance-based doctoral supervisory model to support students in the process of navigating self, agency, and emotions over their doctoral journey. The model emerged through our examination of the lived experiences of three Chinese female doctoral students who, though enrolled as internal students in our New Zealand university, were prevented by the pandemic from returning from their Spring Festival sojourn to China, and continued their study by distance. We employed narrative analysis to deeply engage with their stories shared in diaries and one-on-one interviews, alongside social media interactions. These revealed a strong commitment to study emanating from answerability toward their research projects, already underway, and agentive actions to maintain peer-to-peer academic and emotional support, enabling resilience and reflexivity about personal values and needs. Learning from this experience, we emphasize in our model the need to nurture important bonds between students, their peers and their supervisors in online environments.
Keywords: agency; doctoral supervision; emotions; international students; narrative analysis